2023
DOI: 10.1155/2023/1891759
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Evaluation of the Groundwater Potential in the Fractured Karoo Aquifer Using Magnetic and Electrical Resistivity Methods: Case Study of the Balfour Formation, Alice, South Africa

Gbenga Olamide Adesola,
Oswald Gwavava,
Kuiwu Liu

Abstract: The study is aimed at evaluating the groundwater accumulations present in Alice using magnetic and electrical resistivity measurements to examine the trends of structural elements and characterize the groundwater resource for borehole drilling. The magnetic maps show a low magnetic linear structure moving northwest to southeast direction, which may be caused by fractures. The linear high intensities were probably caused by dolerite dykes, while dolerite sills caused broader high-intensity areas. The depth slic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…This supports that the type of rock is young rock with a discontinuous description (massive rock) which was destroyed by the drill bit during the drilling test [15][24] [23] [25].In the analysis of geoelectric test results and secondary data, as well as the correlation of geological data maps, it was found that the field test results matched the secondary data of geospatial data. At the geoelectric test location, BL 01-BL 06 shows that there are varying layers of soil.…”
Section: Figure 7 Geoelectric Measurement Results At Bh Bl-03 Pointsupporting
confidence: 64%
“…This supports that the type of rock is young rock with a discontinuous description (massive rock) which was destroyed by the drill bit during the drilling test [15][24] [23] [25].In the analysis of geoelectric test results and secondary data, as well as the correlation of geological data maps, it was found that the field test results matched the secondary data of geospatial data. At the geoelectric test location, BL 01-BL 06 shows that there are varying layers of soil.…”
Section: Figure 7 Geoelectric Measurement Results At Bh Bl-03 Pointsupporting
confidence: 64%
“…Over the years, several conventional methods, such as geological, geophysical, and hydrogeological, have been used to identify and explore GWPZ [14][15][16]. Various geophysical methods, such as electromagnetic, seismic refractive, gravity, magnetic, and electrical resistivity techniques, have been utilized in geophysics to explore groundwater [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have shown that diagenetic alterations in siliciclastic rocks influence the reservoir quality by changing the primary porosity and permeability of the rocks [13][14][15][16][17][18][19]. The relationship between fracture, fault, pores, and groundwater potential has been investigated and reported by some researchers [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%